PENERAPAN PEMBELAJARAN KOOPERATIF TIPE GROUP INVESTIGATION UNTUK MENINGKATKAN KETERAMPILAN PROSES SAINS SISWA KELAS VI MIN RUKOH BANDA ACEH - Syahidan Nurdin (PIONIR: JURNAL PENDIDIKAN, 2021)
The purpose of learning science in the KTSP is to develop process skills to investigate the environment, solve problems and make decisions. Students' ability in science process skills will affect students' abilities in learning. Research has been carried out on improving science process skills in learning through the application of group investigations of class VI students at MIN Rukoh Banda Aceh City. This research raises the issue of "How to increase the ability of science process skills through the application of group investigations in class IVMIN Rukoh Banda Aceh". This study aims to improve process skills with group investigations including questioning skills, planning skills, observing skills, and students' communication skills in students' science learning. The subjects in this study were students of class VI MIN Rukoh Banda Aceh, totaling 34 students. This research is a classroom action research (CAR). The results of the study were obtained through worksheets and observations. The results showed that the percentage of classical completeness in the first cycle was 29.41%, and the second cycle was 38.23%. The difference in the percentage of completeness between cycle I and cycle II was 44.12%. Thus, the application of group investigations can improve science process skills in grade VI students at MIN Rukoh Banda Aceh City.